"Comparative Law" and 21st Century Legal Practice: An evolving nexus - BITAS, Basil C. (Institutional Knowledge at Singapore Management University, 2012)
This commentary notes that the demands of modern practice are changing under the stress of “globalisation” as manifested in the increased velocity of communication and commerce and the greater mobility and interconnectedness of individuals. National legal systems and the lawyers and judges administering them are destined to interact with alien legal systems of a national, regional, or supra-national nature in a number of multi-faceted ways. Such trends and developments are exerting a profound effect on the legal environment in Asia. The question then arises as to how legal education should respond to these developments. This commentary argues that the traditional doctrinal curriculum must be balanced by offerings that enhance the perspective of young lawyers and practitioners by instilling in them a practical appreciation of comparative issues. Rather than emphasising rules per se, the comparative approach described in this commentary is designed to sensitise students to the forces shaping the modern practice environment while also giving them an appreciation of the fundamental grammar of external legal systems and of the expanded universe of options for problem-solving. The evolving legal environment will reflect a number of asymmetric interactions between the domestic courts and private dispute resolution fora, the state and regional bodies, and finally between the state and supranational instances and instrumentalities. This commentary suggests that modern legal training must incorporate these complex dimensions of practice into the curriculum by adopting a broader notion of “curriculum” in general and a more flexible view of what we mean by “comparative law” in particular.